Faculty perceptions on objective structured clinical examin dental education = Percepción de los profesores sobre el examen clínico estructurado y su objetivo en la educación dental - Wali, Othman; Vanka, Amit; Vanka, Shanthi (2022)
Structured Clinical Exam (OSCE) uses standardized content and procedures to assess students across multiple domains of learning. The study is aimed to assess knowledge, attitudes, practices and observations of dental faculty on OSCE. The survey was distributed into dental faculty members in randomly selected government and private institutions in Saudi Arabia. The questionnaire was pre-tested and consisted of 4 categories including general characteristics of respondents, knowledge on utility of OSCE in curriculum and it's reliability, attitudes regarding OSCE on a 5 point Likert scale, practices and observations on OSCE on Multiple choice questions (both single answer and multiple answer) and responses on a 5 point Likert scale. The sample size was determined to be 93 and the survey was sent electronically to 10 institutes. 101 complete responses from 7 institutions were considered from the 122 received. Faculty participation in OSCE was high within evaluators 94% (n=94) and administrators 61% (n=61). Majority of respondents (62%) believed that OSCE is most suited for competency based education, to assess cognitive skills (73%) and diagnostic interpretation (79%). Reliability of OSCE can be increased by standardization of evaluators (77%) with highest number believing that 6-8 stations (42%) are the minimum required in an OSCE. Institution guidelines (49%) coupled with workshops (47%) was the preferred method of preparation for OSCE. Majority felt that OSCE is most suitable for high stakes exams (mean=3.37) and it is an indispensable part of dental assessment (mean=3.78). Minimum number of stations for adequate reliability was reported to be lesser that in reported literature, specially so for high stakes assessments. Logistics required for arranging an OSCE and difficulty in standardized patients, may suggest that OSCE should be used in select situations.
El examen clínico estructurado (ECOE) utiliza contenido y procedimientos estandarizados para evaluar a los estudiantes en múltiples dominios de aprendizaje. Este estudio tiene como objetivo evaluar los conocimientos, las actitudes, las prácticas y las observaciones de los profesores de odontología sobre la ECOE. La encuesta se distribuyó a los miembros de la facultad de odontología en instituciones gubernamentales y privadas seleccionadas al azar en Arabia Saudita. El cuestionario se utilizó previamente y constaba de 4 categorías que incluían generalidades de los encuestados, conocimiento sobre la utilidad de la ECOE en el plan de estudios y su confiabilidad, actitudes con respecto a la ECOE en una escala Likert de 5 puntos, prácticas y observaciones sobre la ECOE en preguntas de opción múltiple (ambas respuesta y respuesta múltiple) y respuestas en una escala Likert de 5 puntos. Se determinó el tamaño de la muestra en 93 y la encuesta se envió electrónicamente a 10 institutos. Se consideraron 101 respuestas completas de 7 instituciones. La participación del profesorado en ECOE fue alta entre los evaluadores 94% (n=94) y los administradores 61% (n=61). La mayoría de los encuestados (62%) cree que la ECOE es más adecuada para la educación basada en competencias, para evaluar las habilidades cognitivas (73%) y la interpretación del diagnóstico (79%). La confiabilidad de la ECOE puede aumentarse mediante la estandarización de los evaluadores (77%) y el número más alto cree que 6-8 estaciones (42%) son el mínimo requerido en una ECOE. Las directrices de la institución (49%) junto con los talleres (47%) fue el método preferido de preparación para la ECOE. La mayoría consideró que la ECOE es más adecuada para exámenes de alto riesgo (media=3,37) y es una parte indispensable de la evaluación dental (media=3,78).Se informó que el número mínimo de estaciones para una confiabilidad adecuada es menor que en la literatura...
En revista Odóvtos, vol. 24, no.2 (mayo-agosto 2022)
Descripción basada en el contenido visto el 19 de noviembre, 2024
También disponible en formato HTML y EPUB